Strategic Framework for Green Accounting and Reporting (GAR) - Othman, Radiah; Yusuf, Haslinda; Yatim, Normahiran (Department of Management, Faculty of Economics and Business, Brawijaya University, 2013)
This paper aims to propose a strategic framework for Green Accounting and Reporting (GAR) adoption in Malaysia. Green accounting translates how the management practice and accountable on the effects and uses of the environment. The accountability is reflected through the reporting function which naturally demands for transparency to the stakeholders. Malaysia has a comprehensive regulatory framework for green-related management and practice but unfortunately this has not reflected in the context of local environmental matters where degradation is a persistent problem. A strategic framework is necessary to accompany the governments blue-prints and facilitate companies to adopt GAR. Drawing from the literature, the strategy is based on the firms responsibilities and the impact it has to the industry, country and society at large, at least for two generations.